2018
DOI: 10.1055/s-0038-1625979
|View full text |Cite
|
Sign up to set email alerts
|

Pseudotumor Cerebri Presenting Unilateral Papilledema Associated with Iron-deficiency Anemia

Abstract: Pseudotumor cerebri is a relatively common pathology that is characterized by intracranial hypertension in the absence of mass lesions. It commonly affects young and obese women, and its presentation with visual loss and bilateral papilledema is well-described in the literature. We present a case of a 44-year-old, non-obese, female patient presenting with unilateral papilledema and iron-deficiency anemia. This case emphasizes this unusual presentation and the rare association with iron deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
(62 reference statements)
0
0
1
Order By: Relevance
“…Abducens nerve palsy was not present in our case. Some authors revealed the possible correlation between IICP and iron-deficiency anemia (30). In our case, the patient did not present this type of anemia.…”
Section: Discussioncontrasting
confidence: 40%
“…Abducens nerve palsy was not present in our case. Some authors revealed the possible correlation between IICP and iron-deficiency anemia (30). In our case, the patient did not present this type of anemia.…”
Section: Discussioncontrasting
confidence: 40%